Lower limbs kinematic analysis during a jump landing task in soccer players with unilateral anterior cruciate ligament reconstruction - Ghorbani, M.; Nouri, H.; Heydarian, M.; Mottaghitalab, M.; Zarei, H. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Fatigue leads to an acute decline in muscle strength, altered patterns of lower extremity muscle activation, changes in hip and knee kinematics. In terms of the effects of fatigue on knee joint kinematics during plyometric training, there is still a lack of knowledge regarding kinematic differences between athletes who passed the ACL reconstructions rehabilitation period and healthy athletes. Therefore, this study aimed to compare lower limb joint kinematic parameters between reconstructed cruciate ligament and healthy control soccer players during jump landing in a fatigued setting.